Respuesta :

Answer:

there are 2 answers (1.56 or -2.56)

Step-by-step explanation:

-(2x+x²-1)=-(x+3)

open bracket

-2x-x²+1=-x-3

add x to both sides

-2x+x-x²+1= -3

-x-x²+1= -3

add 3 to both sides

-x-x²+1+3= -3+3

-x²-x+4=0

divide by -

x²+x-4=0

a= 1

b=1

c=-4

x= (-b±√b²-4ac)/2a = (-1±√1²-4(1)(-4))/2(1) = (-1±√1+16))/2= (-1±√17))/2

(-1±√17))/2

(-1+√17))/2              (-1-√17))/2

(-1+4.123)/2            (-1-4.123)/2

3.123/2                      -5.123/2

1.5615                         -2.5615

1.56                                -2.56

1.56 or -2.56